Quality culture at higher learning institutions: Challenges and strategies / Razmah Mahmod, Sharifah Zannierah Syed Marzuki and Che 'Asniza Osman - Mahmod, Razmah; Syed Marzuki, Sharifah Zannierah; Osman, Che ' Asniza (2006)
Government regulatory policy in higher learning institution systems is usually aimed at maximising the quality of higher education given a certain level of demand. Although higher education systems can be seen as buyer-seller markets where academic institutions sell academic education and students buy it, higher education has unique characteristics. It can be seen as a great public interest in the sense that society as a whole benefits culturally, economically and socially, from maintaining high-quality higher education. This is the usual justification for heavy subsidies given to public universities as well as for governmental involvement in controlling and structuring the system. Irrespective of any organisations that wish to embed quality, there are two things to remember: firstly, there must be challenges on implementing and secondly, guidance in which it is equally important to ensure its success. Similarly, when quality wants to be implemented by a university, quality enhancement models such as total quality management need to be fitted coherently with the organisation's culture and structures. Thus, this paper reviews recent research, literature and views of the authors involved in research on quality at higher learning institutions. It is hoped that through constructive criticisms and useful suggestions gathered from the many literature reviews referred, the organisation of UiTM Pahang may able to perceive a broader view of these information and, hence, continuously making effort for the enhancement of quality culture in teaching and learning process.